Connecting cat: a transmedia learning project - Rodrigues, Patrícia (2015)
In this paper we present an overview of a transmedia learning project. As part of an ongoing research project, Connecting Cat provides glimpses of a story taking place in the material, physical world, and the imaginary world through image, sound and text. Specifically targeted to English as Second Language students, the project supports entry points for learning through immersion in an adventure story and engagement in multimodal learning activities.